1999
DOI: 10.1002/(sici)1097-4644(19990701)74:1<74::aid-jcb8>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of testosterone secretion by digitoxin in rat testicular interstitial cells

Abstract: Both in vivo and in vitro experiments were conducted to determined the effects of digitoxin on the secretion of testosterone, and its underlying mechanisms including testicular adenosine 3':5'-cyclic monophosphate (cAMP), and the activities of steroidogenic enzymes. Male rats were injected with digitoxin, human chorionic gonadotropin (hCG), or hCG plus digitoxin via a jugular catheter. Blood samples were collected immediately before and at 30 and 60 min after the challenge, and analyzed for testosterone by rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Estrogen directly can retard pubertal Leydig cells development [41] and inhibit testosterone production [42&43]. The current results are in agreement with the results of Lin et al [8] and Wang et al [44] who suggested that digoxin inhibits the production of testosterone in rat testicular interstitial cells, at least in part, via attenuation of the activities of adenylyl cyclase and cytochrome P450 scc .…”
Section: Endocrine-disrupting Chemicals May Disrupt Endocrine Homeostsupporting
confidence: 90%
“…Estrogen directly can retard pubertal Leydig cells development [41] and inhibit testosterone production [42&43]. The current results are in agreement with the results of Lin et al [8] and Wang et al [44] who suggested that digoxin inhibits the production of testosterone in rat testicular interstitial cells, at least in part, via attenuation of the activities of adenylyl cyclase and cytochrome P450 scc .…”
Section: Endocrine-disrupting Chemicals May Disrupt Endocrine Homeostsupporting
confidence: 90%
“…3a,5a-THP infusions reinstated midbrain levels to that of pro-oestrous rats and had no effect on plasma levels. production (28). Dihydrotestosterone, a 5a-reduced metabolite of testosterone, can be reversibly converted to 3a-androstanediol by the enzyme 3a-HSOR within astrocytes (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of plasma and TIF testosterone were measured by RIA as described elsewhere (Wang et al, 1999;Chiao et al, 2002). The sensitivity of the testosterone RIA was 2 pg per tube.…”
Section: Testosterone Riamentioning
confidence: 99%